2009
DOI: 10.1016/j.surneu.2008.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of clipping vs coiling of intracranial aneurysms after subarachnoid hemorrhage in a developing country—a prospective study

Abstract: Patients with aneurysmal SAH whom we judged to require coiling had higher charges than patients who could be treated by clipping. The benefits of apparent decrease in length of stay in the endovascular group were offset by higher procedure price and cost of consumables. There was no significant difference in clinical outcome at 6 months. We have proposed a risk scoring system to give guidelines regarding the choice of treatment considering size of aneurysm and resource allocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…All these studies originate from developed countries where medical insurance covers most of the medical expenses, and where the per capita income is higher than the world average [15]. They concluded that while the endovascular procedure tended to be more expensive in terms of cost of consumables, this expense was more than compensated by savings in staffing costs, and the period and cost of hospitalization [13, 16–19]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these studies originate from developed countries where medical insurance covers most of the medical expenses, and where the per capita income is higher than the world average [15]. They concluded that while the endovascular procedure tended to be more expensive in terms of cost of consumables, this expense was more than compensated by savings in staffing costs, and the period and cost of hospitalization [13, 16–19]. …”
Section: Discussionmentioning
confidence: 99%
“…In France, it was assessed as 14,477.39 € [12]. In Pakistan, the average cost of endovascular treatment was estimated at € 5080 [13]. …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17] Several studies have analyzed the economic aspects of cerebral aneurysm interventions. [18][19][20][21][22][23] However, the generalizability of their findings is limited because most authors failed to adjust appropriately for measured or unmeasured confounders. Some are single-center [18][19][20] or international experiences [21][22][23] whereas others have utilized charges as a surrogate for cost 24 and are therefore not reflecting the true financial impact of these procedures.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23] However, the generalizability of their findings is limited because most authors failed to adjust appropriately for measured or unmeasured confounders. Some are single-center [18][19][20] or international experiences [21][22][23] whereas others have utilized charges as a surrogate for cost 24 and are therefore not reflecting the true financial impact of these procedures. Several investigators have focused only on hospitalization cost, which does not take into account the cost of possible future reintervention in endovascularly-treated patients or the cost of longterm care in patients experiencing complications.…”
Section: Introductionmentioning
confidence: 99%
“…Some have been retrospective analyses of single institution experiences,6–8 demonstrating results with limited generalization, given their inherent selection bias. Other investigations have focused on patients from the International Subarachnoid Aneurysm Trial study14 or other international centers,3 10 12 13 15 with restricted applicability to the US healthcare market. Multicenter studies based on US data4 5 8 9 11 did not analyze modifiable drivers of cost after CACo or develop a model for cost approximation.…”
Section: Introductionmentioning
confidence: 99%